Mobile Web sebagai Media Perencanaan Perjalanan Wisata Berbasis Kolaborasi untuk Gen Z: Studi Kasus: Pariwisata Pantai Gorontalo - Purnamasari, Dewi Rara Rizky; Ratri, Dianing (Universitas Komputer Indonesia, 2025)
The lack of interactive and visually appealing information about beach tourism destinations in Gorontalo, especially for Generation Z, presents a challenge in catering to this group accustomed to receiving information through social media. Generation Z, as a generation that has grown up in the digital era, tends to rely on online platforms, such as social media, for trip planning and gathering essential information. This study aims to design a mobile tourism website that meets the needs of Gen Z by providing interactive features, such as collaboration tools. The design thinking method was employed, starting with identifying user needs through questionnaires and in-depth interviews. The design results reveal that Gen Z requires interactive, collaborative information and features that allow sharing experiences via social media. The website was designed to align with these needs. Evaluation through user testing demonstrated that the website effectively supports Gen Z in planning their trips. In conclusion, the website not only simplifies trip planning for Gen Z but also accommodates their desire for collaboration with peers during the planning process.